Left Ventricular Pseudoaneurysm: Caused by Coronary Spasm, Myocardial Infarction, and Myocardial Rupture - Mahilmaran, Asha (2002)
We report a very rare case of a 47-year-old man who had coronary spasm that resulted in a silent myocardial infarction, a ruptured myocardial wall, and a nonruptured left ventricular pseudoaneurysm. The patient presented with a 6-month history of dyspnea on exertion, without evidence of fixed coronary artery stenosis. Coronary angiography showed severe coronary spasm of the left anterior descending and left circumflex arteries; the spasm was relieved promptly by nitroglycerin. Echocardiography and left ventricular angiography revealed the large left ventricular pseudoaneurysm posterolateral to the left ventricle. We performed surgical resection of the pseudoaneurysm and patch repair of the ruptured left ventricular wall, with excellent results. We present this case because of the highly unusual sequence of events. Early surgical intervention resulted in the patient's recovery. (Tex Heart Inst J 2002;29:122–5)